Mbah Man White Tofu Factory's marketing mix - Sri Amelia; Ersis Warmansyah Abbas; Raihanah Sari; Syarifudin Syarifudin; Fatwa Nur’aini (Journal of Social Development, 2025)
A microbusiness called Mbah Man's White Tofu Factory uses conventional but reliable marketing techniques. The purpose of this study is to examine how Mbah Man's White Tofu Factory in Gang Pangeran Suryanata, Banjarmasin, applies the marketing mix, which comprises elements of product, price, site, and promotion. This study employs a qualitative descriptive methodology, gathering data via documentation, interviews, and observation. The factory owner, production manager, workers, and distributors are the study's informants. The study's findings show that: The product aspect demonstrates that the factory consistently produces tofu with a dense, soft feel that is difficult to break; Competitive pricing and modifications based on changes in the cost of raw materials are used to implement the price aspect; A direct distribution system and mutual trust between producers and distributors handle the location or distribution aspect; Customer testimonies, verbal promotion, and direct communication are the straightforward methods used to carry out the promotion component. The study's conclusion is that, despite fierce competition in the local market, Mbah Man White Tofu Factory's consistent use of the marketing mix approach is able to sustain business sustainability, boost customer loyalty, and strengthen competitiveness.